Circular - McCleland, Olga Y.
038-0153-001 NATIONAL JOINT COMMITTEE FOR SPANISH RELIEF CHAIRMAN: THE DUCHESS OF ATHOLL, M.P. VICE-CHAIRMEN: THE EARL OF LISTOWEL MISS ELEANOR RATHBONE, M.P. HON. SECRETARIES MR. D.R GRENFELL, M.P. CAPT. J.R.J. MACNAMARA, M.P. MR. WILFRID ROBERTS, M.P. HON. TREASURER: VISCOUNT CECIL OF CHELWOOD, P.C., K.C. HON. ADMINISTRATOR: MR. G.T. GARRATT ORGANISING SECRETARY (BASQUE CHILDREN): MISS BETTY L. ARNE ASSISTANT SECRETARY: MISS OLGA Y. McCLELAND 53, MARSHAM STREET, LONDON, S.W.1 TELEPHONE: VICTORIA 2168 18th March, 1938. TO OFFICERS AND MEMBERS OF THE NATIONAL JOINT COMMITTEE FOR SPANISH RELIEF & THE BASQUE CHILDREN'S COMMITTEE At last night's meeting of the two Committees, the question of holding a London Conference was reconsidered and it was agreed that the Conference proposed for April 2nd and 3rd should be postponed and a One-day Conference held on Saturday, the 9th. The object of this would be to discuss and pool ideas on the best methods of looking after and collecting money for the two thousand children who are likely to be here for some time. It is also hoped that the Officers will be given an opportunity for explaining and discussing the whole question of their relations with the Spanish Government and the Insurgent authorities, and the policy they have adopted as regards returning children to their parents. The proposal is to have two sessions, one on Saturday morning and one in the afternoon. Some representatives of local committees would obviously have to stay in London the previous night and offers of hospitality from Members of the Committees for the visiting delegates would be gratefully received by the Office. Would Committee Members please le us know whether they will be able to attend? Olga Y. McCleland Conference Secretary. 292/946/38/153